Call for the International Workshop Cloud Education Environments - for Papers, Call (International Journal of Advanced Corporate Learning (iJAC), 2012)
This workshop will focus on the exchange of relevant trends and research results, as well as the presentation of practical experiences gained while developing and testing cloud education environments, both from a teaching and a learning perspective. Best papers will be selected for submission of an extended version in a Special Issue on Cloud Education Environments of the Journal of Universal Computer Science. Cloud Learning Environments (CLEs) consider the cloud as a large ecosystem, which is not owned by any educational organization. Within this ecosystem, learners and educators act as the users and producers of cloud-based learning services. They have complete control over the choice, use and sharing of the learning tools and content provided by these services. This approach has the potential to enable and facilitate both formal and informal learning. It allows learners to learn anywhere and at anytime. It also facilitates collaboration among learners and educators. Additionally, the openness, sharing and reusability of learning tools and content on the web are technically enabled and promoted.